INFLUNCE OF GROWTH REGULATORS ON CALLUS INDUCTION OF CITRUS VOLKAMERIANA IN VITRO - & Hamad, Al- Khazali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research was conducted in the plant tissue culture Lab. College of Agriculture / University of Baghdad from February to October 2015. The aim of the study was investigating the influences of combinations of Naphthalene acetic acid (NAA) , Thidiazuron (TDZ) Spermidine (Spd. ) and 2,4-Dichlorophenoxy acetic acid (2,4-D) , Benzyl adenine (BA) on callus induction and adventitous shoot regeneration originated from cotyledon of Citrus volkameriana seeds. Seeds were disinfested with 0.1 % of HgCl2 for 15 minutes. The MS medium supplemented with (0.0,1.5 , 3.0 ) mg L-1 NAA in combination with (0.0, 0.05, 0.1) mg L-1 TDZ and (0.0, 0.5 ,1.0) mg L-1 Spd. and MS medium supplemented with (0.0, 1.5 , 3.0) mg L-1 2,4-D in combination with (0.0 ,1.0 , 2.0 ) mg L-1 BA and (0.0 ,0.5 , 1.0) mg L-1 Spd. the interaction between 1.5 mg L-1 NAA and (0.05 , 0.1) mg L-1 TDZ and the interaction between 3.0 mg L-1 NAA and (0.05 ,0.1) mg L-1 TDZ with all concentrations of Spd. gave the highest percentage of callus induction 100 % . While the MS medium supplemented with 3 mg L-1 of 2,4-D in combination with all concentrations of BA and spd. gave the highest percentage 100 % of callus induction. Results showed that MS medium supplemented with 1.5 mg L-1 NAA in combination with 0.1 mg L-1 TDZ and 1.0 mg L-1 spd. gave the highest values of fresh and dry weight of callus (668.8, 44.59 ) mg respectively . While the MS medium supplemented with 3 mg L-1 2,4-D in combination with 1.0 mg L-1 spd. And 0.0 mg L-1 BA gave the highest values of fresh and dry weight of callus (709.2 , 47.28 ) mg respectively.